Green CP purifier affordable and organic air purifier : utilization of cacao pods as air purifying panels for indoor use - Donado, Nichol Simon D.
Cacao pods is the by-product of cacao industry, the cacao industry produces a lot of waste every year because of the high production of cacao which is used in making chocolates. The high production of waste of cacao industry drives the plant owners to utilize cacao pods. Research shows that the best way to utilize the cacao pods is to convert them into activated charcoal that will make them a good air purifier and odor neutralizer.